A qualitative assessment of factors affecting nursing home caregiving staff experiences during the COVID-19 pandemic. - Rachel L Snyder (Public Library of Science (PLoS), 2021)
Background A large portion of COVID-19 cases and deaths in the United States have occurred in nursing homes; however, current literature including the frontline perspective of staff working in nursing homes is limited. The objective of this qualitative assessment was to better understand what individual and facility level factors may have contributed to the impact of COVID-19 on Certified Nursing Assistants (CNAs) and Environmental Services (EVS) staff working in nursing homes. Methods Based on a simple random sample from the National Healthcare Safety Network (NHSN), 7,520 facilities were emailed invitations requesting one CNA and/or one EVS staff member for participation in a voluntary focus group over Zoom. Facility characteristics were obtained via NHSN and publicly available sources; participant demographics were collected via SurveyMonkey during registration and polling during focus groups. Qualitative information was coded using NVIVO and Excel. Results Throughout April 2021, 23 focus groups including 110 participants from 84 facilities were conducted homogenous by participant role. Staffing problems were a recurring theme reported. Participants often cited the toll the pandemic took on their emotional well-being, describing increased stress, responsibilities, and time needed to complete their jobs. The lack of consistent and systematic guidance resulting in frequently changing infection prevention protocols was also reported across focus groups. Conclusions Addressing concerns of low wages and lack of financial incentives may have the potential to attract and retain employees to help alleviate nursing home staff shortages. Additionally, access to mental health resources could help nursing home staff cope with the emotional burden of the COVID-19 pandemic. These frontline staff members provided invaluable insight and should be included in improvement efforts to support nursing homes recovering from the impact of COVID-19 as well as future pandemic planning.